Prevention of toxic effects of cyclosporin on pancreatic B-cells of rats by Rioprostil, a new prostaglandin analogue. Issue 11 (November 1988) - Müller, M K; Degenhardt, H; Klöppel, G; Goebell, H; Bergmann, K; Löhr, M
Abstract : Cyclosporin 5, 10, and 20 mg/kg bw was given to rats once daily intragastrically and caused a dose dependent, significant decrease of glucose dependent insulin release from the arterially perfused isolated pancreas, without affecting animal behaviour, weight gain, microscopic appearances of the pancreas, or kidney function. Subcutaneous injection of a new synthetic prostaglandin analogue Rioprostil 7.5 micrograms/kg bw twice daily completely prevented the effect of cyclosporin 5 mg/kg bw and protected significantly against the effects of cyclosporin 10 and 20 mg/kg bw.